New Sericosura (Pycnogonida:Ammotheidae) from deep-sea hydrothermal vents in the Southern Ocean - Arango, Claudia P.; Linse, Katrin (Zootaxa, 2015)
Three new species of Sericosura (Pycnogonida: Ammotheidae) are described from recently discovered hydrothermal vents in the East Scotia Ridge, Southern Ocean: Sericosura bamberi sp. nov., S. dimorpha sp. nov. and S. curva sp. nov. The eleven species known to date in the genus Sericosura are all inhabitants of chemosynthetic environments in different oceans around the world.        Morphology and preliminary DNA data from the COI locus suggest the East Scotia Ridge pycnogonids have relatively close evolutionary affinities with species known from the East Pacific Rise and the Mid-Atlantic Ridge. This finding highlights the importance of Sericosura as a characteristic taxon of hydrothermal vents and the great potential of this genus for global scale ecological and evolutionary studies of hydrothermal vents fauna.        The use of pycnogonid DNA data combined with recent models explaining biogeographic provinces along the mid-ocean ridge system should prove extremely useful to understanding the patterns of diversification of endemic fauna from chemosynthetic environments and from the deep-sea in general.